Influence of Area, Age and Sex on Per- and Polyfluorinated Alkyl Substances Detected in Roe Deer Muscle and Liver from Selected Areas of Northern Italy - Susanna Draghi; Giulio Curone; Radmila Pavlovic; Federica Di Cesare; Petra Cagnardi; Claudia Fornesi Silva; Alberto Pellegrini; Federica Riva; Francesco Arioli; Marco Fidani (Animals, 2024)
Due to their physicochemical properties, per- and polyfluorinated alkyl substances (PFASs) persist and bioaccumulate in living organisms, causing adverse health effects. Since exposure to xenobiotics is influenced by factors related to both the living organism and the considered compounds, biomonitoring PFASs’ presence in the environment is of crucial importance. This study aimed to detect and quantify 15 PFASs in the muscle and liver of 40 roe deer from a specific area in Northern Italy by UPLC-HRMS. In the roe deer, liver PFAS concentrations were higher than those seen in muscle (p < 0.05). Although PFAS content in animals from urbanized areas was higher than those found in deer from rural areas, this difference was not statistically significant. In female roe deer, the concentration was higher than in males (p < 0.05); moreover, older animals showed higher concentrations of PFASs in the liver than younger animals (p < 0.05). In conclusion, the amount of PFASs was higher in tissues from roe deer belonging to urbanized areas, showing that this species might serve as a good bioindicator due to its territorial behavior. PFAS content was significantly higher in female roe deer, although the reason is not fully known. Finally, PFAS concentration was higher in the liver of older animals, probably due to compromised hepatic function.